Gems of geometry - Barnes, John (Springer Berlin Heidelberg, 2012)
Based on a series of lectures for adult students at Reading and Oxford University in the UK, this lively and entertaining book proves that, far from being a dusty, dull subject, geometry is in fact full of beauty and fascination. The author's infectious enthusiasm is put to use in explaining a range of topics, starting with the Golden Number and taking the reader on a geometrical journey covering topics such as Shapes and Solids, the Fourth Dimension, Projective Geometry and Topology, Chaos and Fractals, Steiner's porism, Soddy's Hexlet, Einstein's Theories of Relativity and finishing up with the amazing world of Crystals.   Aimed at a general readership, and requiring only a basic understanding of mathematics, the text includes a wealth of the author's own diagrams and illustrations, of which many are in stereo.   Equally ideal as an educational gift for a youngster or as a nostalgic journey back into the world of mathematics for older readers, John Barnes' book brings enlightenment and entertainment.    "... unlike your average student textbook, this is a book designed to be dipped into, explored, enjoyed and savoured." PLUS.MATHS.ORG "Gems of Geometry is a delightful little book; it is exactly the kind of thing that I would have loved to have had as a child" Roger Penrose